Wake Up, Work on Dreams, Back to Bed and Lucid Dream: A Sleep Laboratory Study - Erlacher, Daniel; Stumbrys, Tadas (Frontiers in Psychology, 2020)
Lucid dreaming offers many opportunities to study consciousness processes. However, laboratory research in this area is limited because frequent lucid dreamers are rare. Several studies demonstrated that different methods of induction could increase the number of lucid dreams. In four field studies, a combination of a wake-up-back-to-bed (WBTB) sleep protocol and a mnemonic technique (MILD) showed promising results. To further investigate the effectiveness of this combined approach, we conducted a sleep laboratory experiment with four different conditions. The general experimental procedure was the following: Participants were awakened after 6 h of sleep from a subsequent REM period and kept awake for 30 or 60 min, during which they were asked to practice MILD or a control task (e.g., reading). Then they returned to bed for a morning sleep period. In the first condition eleven sport students, who attended a seminar on sleep and dreams, spent one night in a sleep laboratory. To avoid biases due to the seminar attendance (e.g., higher motivation), in the second condition 15 participants who did not attend the seminar were recruited. In the third condition, 14 sport students were tested with a shorter awakening period (30 min). Finally, the fourth condition served as a control condition, whereas eleven sport students slept two non-consecutive nights in a laboratory. Instead of MILD, in one night the participants read a book (fiction, unrelated to dreams), while in the other night they played a Nintendo Wii video game. In the first three conditions, six (54%), eight (53%), and five participants (36%) reported lucid dreams during the morning sleep period, whereas three, (27%), four (27%), and two participants (14%) produced PSG-verified eye signals. In contrast, in the reading condition, only one (9%) participant reported lucid dreams and no eye movements. No lucid dreams were observed in the Wii condition. The findings of the present study show that by using a combination of WBTB and MILD, lucid dreams can be effectively induced in people who are not selected for their lucid dream abilities.